Structural and Functional Connectivity Between the Amygdala and Orbital Frontal Cortex in Burning Mouth Syndrome: An fMRI Study - Tan, Ying; Wu, Xunhua; Chen, Jing; Kong, Lingyu; Qian, Zhaoxin (Frontiers in Psychology, 2019)
With a burning sensation in the tongue or other oral sites in the absence of observable lesions or laboratory findings, burning mouth syndrome (BMS) is a chronic intraoral pain disorder. Previous stud have suggested the brain change in BMS, however, limited number of participants of these studies did not allow us to draw concrete conclusions. The present study aimed to further understanding the brain anatomical and functional changes of BMS with a relatively large sample. Fifty-three patients (26 BMS patients and 27 gender- and age-matched controls) were recruited. Participants came to complete the behavior interview, and performed the MRI scan in the same day. Results revealed that BMS patients had higher depression and anxiety than controls. BMS Patients showed lower GMV in bilateral VMPFC and increased functional connectivity with this region to bilateral amygdala. The brain measures could predict the years of symptom in the BMS group. These results may suggest the neuro-marker for diagnose and treatment of BMS.